Moderasi Beragama melalui Keteladanan Dakwah Walisongo dan Pendidikan Islam di Madrasah Ibtidaiyah Negeri 2 Kota Bengkulu - Nurhasanah Nurhasanah; Alimni Alimni (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: Evaluation of Islamic-Based Education and Training in Excellent Service Training Using the Kirkpatrick Model Moderation is the middle way that is not too extreme to the right or extreme to the left, this is in accordance with the core teachings of Islam which are in harmony with human nature, therefore Muslims are called ummatan washathan, a harmonious and balanced people. The purpose of this study was to determine the urgency of religious moderation through exemplary da'wah walisongo and Islamic education in Madrasah Ibtidaiyah Negeri 2 Bengkulu City. The focus of this research discusses the role of PAI teachers in instilling religious moderation to students through exemplary dakwah walisongo. The research method uses descriptive qualitative. Data collection techniques used are observation, interviews and documentation. Data analysis using the Miles and Huberman model analysis includes (1) data reduction; (2) data presentation; (3) conclusion drawing. The results showed that from the process of teaching and learning activities of MIN 2 Bengkulu City students in Islamic Culture History lessons in the second semester of 2023 dakwah walisongo material, students were able to absorb, understand and implement learning outcomes so that students' understanding of religious moderation increased as a manifestation of Islam rahmatan lil'alamin. The research conclusion reveals that through SKI learning, it can increase students' understanding of the concept of religious moderation as a manifestation of Rahmatan Lil'alamin Islam by emulating the preaching methods of the walisongo.Abstrak: Moderasi Beragama melalui Keteladanan Dakwah Walisongo dan Pendidikan Islam di Madrasah Ibtidaiyah Negeri 2 Kota BengkuluModerasi adalah jalan pertengahan yaitu tidak terlalu ekstrim ke kanan ataupun ekstrim ke kiri, hal ini sesuai dengan inti ajaran Islam yang selaras dengan fitrah manusia, karena itu umat Islam disebut ummatan washathan, umat yang serasi dan seimbang. Tujuan penelitian ini untuk mengetahui urgen si moderasi beragama melalui keteladanan dakwah walisongo dan pendidikan islam di Madrasah Ibtidaiyah Negeri 2 Kota Bengkulu. Fokus penelitian ini membahasa pran guru PAI dalam menanamkan moderasi beragama kepada siswa melalui keteladanan dakwah walisongo. Metode penelitian menggunakan kualitatif deskriptif. teknik pengumpulan data yang digunakan yaitu observasi, wawancara dan dokumentasi. Analisis data menggunakan analisis model Model Miles dan Huberman meliputi (1) reduksi data; (2) penyajian data; (3) Penarikan kesimpulan. Hasil penelitian menunjukkan Dari proses kegiatan belajar mengajar siswa MIN 2 Kota Bengkulu pada pelajaran Sejarah Kebudayaan Islam semester II tahun 2023 materi dakwah walisongo peserta didik mampu menyerap, memahami serta melaksanakan hasil pembelajaran sehingga pemahaman siswa akan moderasi beragama semakin meningkat sebagai perwujudan islam rahmatan lil’alamin. Kesimpulan penelitian mengungkap bahwa melalui pembelajaran SKI tersebut dapat meningkatkan pemahaman peserta didik tentang konsep moderasi beragama sebagai perwujudan bentuk Islam Rahmatan Lil’alamin dengan cara meneladani metode berdakwah dari walisongo.